The Efforts to Increase Community Financial Literacy in Palm Oil Farmer Groups - Rafidah, Rafidah; Arfan, Arfan; Usdeldi, Usdeldi; Rosmanidar, Elyanti; Rahma, Sri; Ramadhan, Argianov; Iqbal, Muhammad; Hardi, Eja Armaz (PT Inovasi Pratama Internasional, 2024)
Increasing financial literacy is an important aspect in supporting the economic welfare of society, especially among farmer groups. This research aims to evaluate the socialization efforts implemented to increase financial literacy in oil palm farmer groups. The methodology used involves a qualitative approach with in-depth interviews and observations of farmer group members in several locations. The research results show that although there has been an increase in financial knowledge among members, there are still significant challenges regarding the application of this knowledge in daily practice. Factors such as lack of facilities and technological support, as well as limited access to information, are the main obstacles. This research suggests the need for the development of more structured training programs and ongoing support to facilitate the effective implementation of financial knowledge in the field. By increasing financial literacy, it is hoped that oil palm farmer groups can manage their resources better and improve their overall economic welfar